Penerapan Metode MABAC dengan Pembobotan ROC Dalam Sistem Pendukung Keputusan Pemilihan Pengajar dengan Kinerja Terbaik - Kraugusteeliana, Kraugusteeliana; Zen, Agustian; Suryani, Suryani; Alam, Sitti Nur; Winarno, Edy (Building of Informatics, Technology and Science (BITS), 2023)
Selection of the best teacher is one of the problems in a decision making according to semi-structured criteria. In this research, the decision support system explains how the process of selecting alternative teachers who have the best performance in elementary schools applies the MABAC method and weights it using the Rank Order Centroid (ROC) method. The use of this method can solve the problem of determining the best teacher that occurs in elementary schools. The final result of completing the method will produce the highest ranking value which will be determined to be the highest alternative. The data used in this study were 10 alternative teacher data using 5 criteria, resulting in 1 highest ranking of the 10 alternatives obtained by alternative 1 named Servin Manullang with a value of 0.6086 as a recommendation for the teacher with the best performance